Technical Feasibility of Natural Antioxidant Recovery from the Mixture of the Inedible Fractions of Vegetables Produced in a Wholesale Market [Factibilidad Técnica de Recuperación de Antioxidantes Naturales a Partir de la Mezcla de Las Fracciones No Comestibles de Verduras Producidas en Un Mercado Mayorista] - Contreras-Villacura, E; Sepulveda-Cuevas, L; Cerro-Munoz, D (Taylor and Francis Ltd., 2021)
The study evaluated the technical feasibility of directly using the mixture of the inedible fractions of vegetables collected in a wholesale market, for the recovery of a (poly)-phenolic extract with antioxidant capacity. First, the characterization of the leaves and stems of broccoli, celery, carrots, beetroots, cauliflower and cabbage was carried out. Subsequently, the technical feasibility of the recovery of antioxidant compounds from the mixture of these vegetables was analyzed, using a fractional factorial design tailored for screening of the process conditions. Finally, a freeze-dried powdered product was obtained from the extract previously concentrated by vacuum evaporation. The results showed that the product had a total phenolic content of 1752 ± 58 GAE/100 g and antioxidant capacity of 1020 ± 44 mg Fe2+/100 g of dry powder. These inedible vegetable wastes could be an attractive source of natural antioxidants to obtain high added-value products with diverse uses as food and feed techno-functional ingredients. © 2021 The Author(s). Published with license by Taylor & Francis Group, LLC.